Unraveling the mysteries of protein folding and misfolding - Heath Ecroyd; John A. Carver (2008)
Abstract This mini‐review focuses on the processes and consequences of protein folding and misfolding. The latter process often leads to protein aggregation and precipitation with the aggregates adopting either highly ordered (amyloid fibril) or disordered (amorphous) forms. In particular, the amyloid fibril is discussed because this form has gained considerable notoriety due to its close links to a variety of debilitating diseases including Alzheimer's, Parkinson's, Huntington's, and Creutzfeldt‐Jakob diseases, and type‐II diabetes. In each of these diseases a different protein forms fibrils, yet the fibrils formed have a very similar structure. The mechanism by which fibrils form, fibril structure, and the cytotoxicity associated with fibril formation are discussed. The generic nature of amyloid fibril structure suggests that a common target may be accessible to treat amyloid fibril‐associated diseases. As such, the ability of some molecules, for example, the small heat‐shock family of molecular chaperone proteins, to inhibit fibril formation is of interest due to their therapeutic potential. © 2008 IUBMB IUBMB Life, 60(12): 769–774, 2008